2014
DOI: 10.1007/s10103-014-1700-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effect of curcumin-photodynamic antimicrobial chemotherapy in adolescents during fixed orthodontic treatment: a single-blind randomized clinical trial study

Abstract: White spot lesions are one of the concerns during the fixed orthodontic treatment. Thus, the aim of the present study was to evaluate the antimicrobial/anti-inflammatory effect of curcumin-photodynamic antimicrobial chemotherapy (c-PACT) and chlorhexidine varnish on the plaque accumulation and gingival bleeding in adolescents under fixed orthodontic treatment. A randomized clinical trial was performed with an initial number of 45 patients being distributed into three groups: group I-chlorhexidine varnish 2%, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
0
27
0
2
Order By: Relevance
“…Treatments were performed four consecutive times with an interval of 1 week each. The gingivitis condition as measured by gingival bleeding index was reduced statistically significantly in the two groups compared with placebo [37].…”
Section: Gingivitismentioning
confidence: 84%
“…Treatments were performed four consecutive times with an interval of 1 week each. The gingivitis condition as measured by gingival bleeding index was reduced statistically significantly in the two groups compared with placebo [37].…”
Section: Gingivitismentioning
confidence: 84%
“…Several investigations have evaluated the antimicrobial effect against oral bacteria [9][10][11][12][13][14][15]24,43,44], fungi [7,8,25] and strains resistant to conventional drugs [6]. Some studies have assessed the PDI efficacy in pathogens that can also be related with systemic conditions such as Enterococcus faecalis (Ef) [42,[45][46][47][48][49][50] and Escherichia coli (Ec) [45][46][47]49].…”
Section: Antimicrobial Efficacy Of Cur-mediated Pdimentioning
confidence: 99%
“…Most in vitro tests (86.36%) were conducted using planktonic cultures of the microorganisms [6][7][8]10,12,13,15,41,[43][44][45][46][47][48][49], followed by investigations on single-species [6][7][8]42,43,48,50] and multi-species [11] biofilms. Additionally, one animal study [25] and three clinical trials were found [9,14,24]. CUR protocols vary widely among studies, which possibly explain the different results observed in some cases.…”
Section: Antimicrobial Efficacy Of Cur-mediated Pdimentioning
confidence: 99%
See 2 more Smart Citations